2021
DOI: 10.1021/acscatal.1c04594
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbene-Photocatalyzed Tricomponent Regioselective 1,2-Diacylation of Alkenes Illuminates the Mechanistic Details of the Electron Donor–Acceptor Complex-Mediated Radical Relay Processes

Abstract: Progress in the development of photocatalytic reactions requires a detailed understanding of the mechanisms underpinning the observed reactivity, yet mechanistic details of many photocatalytic systems, especially those that involve electron donor–acceptor complexes, have remained elusive. We report herein the development and a combined mechanistic and computational study of photocatalytic alkene 1,2-diacylation that enables a regioselective installation of two different acyl groups, establishing direct, tricom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…The Synopsis will be organized into two categories: examples of EDA complexes with catalytic donors and examples with catalytic acceptors. Recent progress has also been made in engaging catalytically generated intermediates in EDA complex formation, such as enamine- or iminium-ion-based intermediates produced in organocatalysis or N -heterocyclic carbene catalyst-derived intermediates; however these examples will not be discussed herein.…”
mentioning
confidence: 99%
“…The Synopsis will be organized into two categories: examples of EDA complexes with catalytic donors and examples with catalytic acceptors. Recent progress has also been made in engaging catalytically generated intermediates in EDA complex formation, such as enamine- or iminium-ion-based intermediates produced in organocatalysis or N -heterocyclic carbene catalyst-derived intermediates; however these examples will not be discussed herein.…”
mentioning
confidence: 99%
“…Ohmiya et al unmasked a new scheme for activating aldehydes, which can reduce a series of substrates by using Breslow intermediates as electron donors under light or heat induction. Based on the above strategy, Larionov (Scheme ) et al reported the development of a three-component, regioselective olefin 1,2-diacylation reaction through the formation of an EDA complex with photoinduced oxime ester and Breslow intermediate by the transfer of a single electron. Although these works are representative and prospective, the addition of olefin from different acyl sources is difficult to easily achieve, which limits its application in synthetic chemistry to a certain extent.…”
mentioning
confidence: 99%
“…25 Larionov developed a NHC-6 catalyzed regioselective 1, 2diacylation of alkenes with o-diketone derived oximes which afforded direct access to 1, 4-diketones in 42-99% yields (Scheme 14). 26 The requirement of light illumination makes it different from the previous protocols carried out under thermal condition. The author proposed that NHC-derived ketyl radical was formed via an inner-sphere electron-transfer process of the EDA complex between the Breslow intermediate and the oxime acceptor.…”
Section: Scheme 12 Nhc-catalyzed Ring-opening Acylation Of Oxime Deri...mentioning
confidence: 99%
“…Scheme 13 NHC-catalyzed ring-opening conjugative cross-coupling of aldehydes with oxime derivatives 24 Scheme 14 NHC-catalyzed light-induced 1,2-diacylation of alkenes 26 1,5-Hydrogen atom transfer is a classic strategy for cleaving inert C(sp 3 )−H bond, which is used extensively for radical-based transformations. 27 Combining 1,5-hydrogen atom transfer and NHC-catalyzed radical cross-coupling, a N-fluorocarboxamidedirected remote benzylic C-H acylation with aldehydes in the presence of catalyst NHC-7 was established by Xu (Scheme 15).…”
Section: Scheme 12 Nhc-catalyzed Ring-opening Acylation Of Oxime Deri...mentioning
confidence: 99%
See 1 more Smart Citation